Discourse on the shifting of local beauty: Concepts in an Easternization era - Diana Puspitasari; Yudi Suryadi (Faculty of Social and Political Science, Universitas Airlangga, 2020)
The desire to be beautiful among Indonesian women today is influenced by the construction of beauty from outside of the culture. The popular culture of parts of East Asia has entered Indonesia and the Eastern concept of beauty has brought in a different paradigm compared to the local beauty of the Indonesian people. This study is a descriptive qualitative study involving discourse analysis that examines the shift in the construction of beauty held by Indonesian women in the decades 1990-2000 and 2001-2010 through the cosmetic advertisements that appeared on television. Through this research, the shift in the concept of beauty and the discourse hidden behind the present construction of beauty will be revealed. The results found that in the early 1990s, Indonesian women were still oriented towards the reality of the condition that Indonesian women’s skin is tanned. This shifted to the concept of fair skin being preferred using traditional ethnic materials in Indonesia. From the 2000s up until the present, the increasingly popular culture of Japan and Korea has made Indonesian women want white skin like Japanese and Korean women. The change is driven by the desire to be beautiful by those who have experienced the shift in the discourse and beauty concept. Capitalists, as the owners of capital, always want to reap the benefits of every phenomenon that occurs in society. The use of different taglines on the beauty products is a beauty discourse construction strategy in itself and it is a form of symbolic violence against women.